The economic progress of American Jewry: from 18th century merchants to 21st century professionals - Barry R. Chiswick (Institute for the Study of Labor (IZA), 2009)
This paper tracks the economic status of American Jewry over the past three centuries. It relies on qualitative material in the early period and quantitative data since 1890. The primary focus is on the occupational status of Jewish men and women, compared to non-Jews, with additional analyses of earnings, self-employment, and wealth. The Jews in Colonial America, many of Sephardic origin, disproportionately lived in the east coast seaports and were engaged in international trade and finance. The mid-19th century German Jewish immigrants settled throughout the country; often beginning as itinerant peddlers, they advanced to small businesses, and some to not so small businesses in the retail trade. The Yiddish-speaking Eastern European and Russian Jewish immigrants, who arrived primarily in the four decades starting in 1881, are the ancestors of most contemporary American Jews. Starting in operative, craft and laborer jobs in small scale manufacturing or in retail trade in the northern and midwestern industrial cities, they experienced rapid economic advancement. Over the course of the 20th century their descendants achieved very impressive improvements in earnings and occupational status, attaining significantly higher levels than those of the non-Jewish white population. By the year 2000, 53 percent of Jewish men compared to 20 percent of white non-Jewish men were in professional occupations. Among working women in 2000, 51 percent of the Jewish women and 28 percent of non-Jewish white women were in professional jobs. Differences by gender were smaller than differences by religion. Other determinants of earnings the same, including schooling, American Jewish men earned about 16 percent more than other white men, an advantage that is about 8 percent when major occupational group is also held constant. American Jews, from the earliest period to the present, have had high rates of self-employment compared to the non-farm white population of the United States. The nature of this self-employment has changed over time, and currently includes many self-employed professionals. The high level of human wealth of contemporary American Jews is not at the expense of non-human wealth. Overall, and even when other variables including schooling are held constant, Jews have higher levels of wealth and higher rates of wealth accumulation than other religious groups. In summary, over the 350 years since the first Jews settled in what is now the United States, American Jews have consistently demonstrated a very high level of economic achievement.
Keywords: J15; J24; J31; J61; J62; N31; N32; Z12; 330; Jews; immigrants; occupations; earnings; self-employment; wealth; Juden; Erwerbsstatus; Erwerbsverlauf; Migranten; Handelsberufe; Freie Berufe; Vermögen; Einkommen; Sozialgeschichte; USA